2016
DOI: 10.1152/ajpgi.00311.2015
|View full text |Cite
|
Sign up to set email alerts
|

JAK inhibition using tofacitinib for inflammatory bowel disease treatment: a hub for multiple inflammatory cytokines

Abstract: Danese S, Grisham M, Hodge J, Telliez J-B. JAK inhibition using tofacitinib for inflammatory bowel disease treatment: a hub for multiple inflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(103 citation statements)
references
References 82 publications
1
95
0
7
Order By: Relevance
“…Tofacitinib is a potent inhibitor of JAK1 and JAK3. 14 A phase II study, 15 and two identical phase III studies, 16 demonstrated that patients with moderately to severely active UC receiving tofacitinib were more likely to achieve remission at 8 weeks than those receiving placebo. A previous 4-week phase II study, carried out in patients with moderate-to-severe CD, did not show efficacy for tofacitinib 1, 5 or 15 mg twice daily in inducing clinical response; however, a surprisingly high placebo response was observed.…”
Section: Significance Of This Studymentioning
confidence: 99%
“…Tofacitinib is a potent inhibitor of JAK1 and JAK3. 14 A phase II study, 15 and two identical phase III studies, 16 demonstrated that patients with moderately to severely active UC receiving tofacitinib were more likely to achieve remission at 8 weeks than those receiving placebo. A previous 4-week phase II study, carried out in patients with moderate-to-severe CD, did not show efficacy for tofacitinib 1, 5 or 15 mg twice daily in inducing clinical response; however, a surprisingly high placebo response was observed.…”
Section: Significance Of This Studymentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) is an intricate multifactorial, chronic, and relapsing disease that involves inflammation of the gastrointestinal tract [1, 2]. It comprises ulcerative colitis (UC) and Crohn’s disease (CD) triggered through various genetic and environmental elements [35].…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, four JAK families of enzymes (JAK1, JAK2, JAK3 and tyrosine kinase 2) and seven STAT family members (STAT1, STAT2, STAT3, STAT4, STAT5a, STAT5b and STAT6) are employed by over 50 cytokines and growth factors to mediate intracellular signalling . Janus kinase inhibitors are being developed and utilized for the treatment of a variety of inflammatory, autoimmune and haematological disorders in humans …”
Section: Introductionmentioning
confidence: 99%